Supplement to The influence of changing seawater Ca concentration on Elements/Ca ratios in planktonic foraminifera: a culture experiment - AGU G3 - Le Houedec, S (via Mendeley Data) (2020)
Resume table of planktic foraminifera G. siphonifera culture